2022
DOI: 10.1017/s1041610222000680
|View full text |Cite
|
Sign up to set email alerts
|

Sense of purpose as a potential buffer between mental health and subjective cognitive decline

Abstract: Objectives: Purposeful adults may experience greater cognitive resilience because sense of purpose may help buffer against the effects of depressive symptoms and loneliness. We also evaluated whether these associations differed by race. Design: This study uses a wave of self-report data from the SPAN study of psychosocial aging. Setting: Participants come from a representative sample of older adults in St. Louis. Participants: Participants (N = 595) ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
2
5
0
Order By: Relevance
“…Future research could address whether purpose in life buffers the association between loneliness and depressive symptoms, as was the case with cognitive symptoms. The findings of Pfund et al (2022) are also consistent with recent research from our group published in International Psychogeriatrics (Sutin et al, 2022b) on the role of purpose in healthier cognition. Specifically, we examined the relation between purpose and both verbal fluency and episodic memory measured with standard cognitive tasks.…”
supporting
confidence: 89%
See 3 more Smart Citations
“…Future research could address whether purpose in life buffers the association between loneliness and depressive symptoms, as was the case with cognitive symptoms. The findings of Pfund et al (2022) are also consistent with recent research from our group published in International Psychogeriatrics (Sutin et al, 2022b) on the role of purpose in healthier cognition. Specifically, we examined the relation between purpose and both verbal fluency and episodic memory measured with standard cognitive tasks.…”
supporting
confidence: 89%
“…The findings from Pfund et al (2022) build nicely on research recently published in International Psychogeriatrics. A review of the literature on loneliness and depression in a recent issue of International Psychogeriatrics, for example, evaluated the evidence for loneliness as a prospective predictor of depressive symptoms and clinical depression in longitudinal studies.…”
supporting
confidence: 68%
See 2 more Smart Citations
“…Correspondingly, studies show that individuals with a number of psychiatric conditions report lower purpose in life ratings than controls. Furthermore, over time, having greater purpose in life may be protective against the development of depressive symptom (Echeverria et al, 2021), suicidal ideation (Straus et al, 2019), and subjective cognitive decline (Pfund et al, 2022). With regard to specific disorders, patients with schizophrenia report lower purpose in life than control subjects (Strauss et al, 2012); in one study, only 27% were found to have a definite purpose in life (Haq et al, 2009).…”
Section: Impact Of Purpose In Life On General Medical and Mental Heal...mentioning
confidence: 99%